La civiltà comunale italiana nella storiografia internazionale - Andrea Zorzi (Biblioteca di storia, 2008)
This book contains the proceedings of the first international conference organised by the Centro di Studi sulla civiltà comunale of the University of Florence, and offers a fine overview of the contribution made by international historiography to the history of the Italian Comunes. One of the most significant periods in the country's past is addressed here by some of the leading international specialists through the reconstruction of the approaches, issues and outcomes of the principal foreign historiographies (German, French, American, Spanish and English). The result is a fairly articulated picture of how the civilisation of the Comune has been treated and appraised over time outside Italy. Consequently, the book is offered as an updated tool of historiographic reflection and as a useful yardstick for studies devoted to the European urban world.